Recent Trends and Issues in International Student Mobility - De Wit, Hans (International Higher Education, 2010)
Institutions of higher education recently emphasized a view of international students as a source of income generation. Like the UK and Australia, other countries have also introduced out of state fees for international students. The competition for international students has increased even among traditionally sending countries. Selected recruitment of top talents is also a trend. Reputation and employability are the pull-factors for international students: in turn, "brain drain" is a problem in developing countries at the end of the chain.